LEAPmbr enables wastewater reuse for drought-stricken city. Issue 10 (October 2015) - Unknown
Abstract : With chronic droughts and population growth reducing reservoir levels to 30% capacity in Abilene, Texas, USA, the city recently completed the installation of General Electric Co's LEAPmbr membrane bioreactor (MBR) wastewater treatment system as part of major upgrades to the Hamby Wastewater Treatment Plant (WWTP).